2018
DOI: 10.1155/2018/1094352
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Transcutaneous Electrical Nerve Stimulation on Proinflammatory Cytokines: Systematic Review and Meta-Analysis

Abstract: The mechanism of pain reduction involves bidirectional processes of pain blocking (nociception) and reductions in the levels of proinflammatory cytokines in the blood. Does transcutaneous electrical nerve stimulation (TENS) reduce blood levels of proinflammatory cytokines? For this systematic review, we searched in six databases to identify randomized controlled trials with the criteria: humans older than 18 years (adults), use of TENS in the experimental group, and having at least one pre- and postinterventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 47 publications
(96 reference statements)
0
19
0
1
Order By: Relevance
“…stimulate acupoints or sites on the surface of the body, which have the advantages of being safe, easy to use, and digitally operated. Studies have further shown that TENS/TEAS can treat many types of pain [116], including inflammatory pain [117] with satisfactory results [118]. A clinical study had also revealed that TEAS could decrease the levels of CXCL8, IL-1, IL-6, TNFα, and CCL2 to relieve inflammatory responses and decrease the injuries caused by lower limb ischemia-reperfusion [119].…”
Section: Recommendations For Future Researchesmentioning
confidence: 99%
“…stimulate acupoints or sites on the surface of the body, which have the advantages of being safe, easy to use, and digitally operated. Studies have further shown that TENS/TEAS can treat many types of pain [116], including inflammatory pain [117] with satisfactory results [118]. A clinical study had also revealed that TEAS could decrease the levels of CXCL8, IL-1, IL-6, TNFα, and CCL2 to relieve inflammatory responses and decrease the injuries caused by lower limb ischemia-reperfusion [119].…”
Section: Recommendations For Future Researchesmentioning
confidence: 99%
“…Furthermore, although Fiorelli et al was the only study to evaluate serum cytokine level reductions, this does suggest that TENS influences postoperative inflammation and hyperalgesia (15). A recent systematic review and meta‐analysis published in 2018 similarly supports these findings, which provides molecular evidence that TENS is effective in reducing postoperative inflammation (34).…”
Section: Discussionmentioning
confidence: 71%
“…Heat, massage, and exercise improve blood flow to affected areas, which increases tissue perfusion and oxygenation and enhances the removal of inflammatory mediators that promote cellular dysfunction [ 45 , 61 , 64 ]. The reduction in pain symptoms associated with TENS and exercise may be explained by decreases in pro-inflammatory cytokines and the release of endogenous opioids and serotonin [ 71 , 83 , 84 ]. In addition, heat therapy, massage, and TENS may reduce symptoms through stimulation of larger nerve fibers which influences pain perception [ 44 46 , 84 ].…”
Section: Discussionmentioning
confidence: 99%